Criticism of Sharia Banks in Indonesia (an Analysis of Zaim Saidi's Thoughts) - Zain, Zainur; Kamal, Jaidil; Rahmawati, Indah (Universitas Trunojoyo Madura, 2024)
Zaim Saidi, in his academic argumentation, states that current banking practices are in a state of comfort, resulting in the neglect of several sharia provisions under the argument that they are not yet prepared to implement them because they are still in a transitional period. Subsequently, Zaim Saidi asserted that Islamic banking and conventional banking are not entirely equivalent, but rather only 99.9% so. Islamic institutions may be exempt from the interest system; however, it is nearly impossible to be exempt from the usury system. The research question is as follows: